2021
DOI: 10.1038/d41586-021-00209-6
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning made easy for optimizing chemical reactions

Abstract: Debilitating gut pain is common, but the underlying cause is often unclear. It emerges that gut infection triggers localized immune responses that cause normally innocuous foods to be perceived as harmful, leading to persistent pain. See p.151

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Bayesian optimization, the iterative response global optimization algorithm, has demonstrated exceptional performance for tuning machine learning models by optimizing the hyperparameters of models. [ 21 ] We applied Bayesian optimization to explore the hyperparameter space using fivefold cross‐validation with GPyOpt library, through which RMSE were minimized (Note S2 and Figure S5, Supporting Information). For each independent experiment, the statistical mean values for each experiment were used to build a dataset.…”
Section: Resultsmentioning
confidence: 99%
“…Bayesian optimization, the iterative response global optimization algorithm, has demonstrated exceptional performance for tuning machine learning models by optimizing the hyperparameters of models. [ 21 ] We applied Bayesian optimization to explore the hyperparameter space using fivefold cross‐validation with GPyOpt library, through which RMSE were minimized (Note S2 and Figure S5, Supporting Information). For each independent experiment, the statistical mean values for each experiment were used to build a dataset.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, another type of metabolic pathway we can examine is the production pathways; their modeling would allow the development of an optimized overall process. In fact, another study revealed that ML methods can accelerate the optimization of chemical synthesis (Hein, 2021). As stated before, we do not need to enlarge this dataset, which is composed of records of the various parameters of an industrial-scale penicillin fermentation process.…”
Section: Non-linear Machine Learning Methods Are Efficient For Flux P...mentioning
confidence: 99%
“…This will make it easier to deeply understand the basic mechanism, and provide an opportunity to discover a new reaction. Machine learning techniques make it possible to identify laws from data. Therefore, machine learning is used to build data error analysis and calibration models for improving the precision and confidence of experimental data, achieving effective detection of weak reactions.…”
Section: Introductionmentioning
confidence: 99%